Feasibility of Inquiry-Based Science E-Module Guided by Material Interaction of Living Beings with Environmental Learning Resources to Improve Science Literacy - Lilis Eka Herdiana; Widha Sunarno; Meti Indrowati (Postgraduate, University of Mataram, 2022)
This type of research is development research that aims to determine the feasibility of the E-Module for the Interaction of living beings based on guided inquiry to improve the science literacy of grade VII students. The development model refers to the Borg and Gall development model with modifications as needed in the field consisting of 9 stages, namely: Research and information collecting, Planning, Developing a preliminary form of product, Preliminary feed testing, Main product revision, Main field testing, Operational product revision, Operational field testing, E-module final product. The instruments used are feasibility assessment sheets of material experts, media experts, linguists, and learning experts. The research found that the guided inquiry-based E-module material on the Interaction of living beings with environmental learning resources is suitable for learning